Long-term gene therapy with Del1 fragment using nonviral vectors in mice with explanted tumors - Kitano, Hisataka (Onco Targets Ther, 2016)
Cancer gene therapy using nonviral vectors is useful for long periods of treatment because such vectors are both safe and inexpensive, and thus can be used repeatedly. It has been reported that gene therapy with an E3C1 fragment of Del1 in a mouse explanted tumor model improved prognosis. The present study aimed to analyze the long-term effects of repeated non-viral gene transfer of E3C1. Mice with explanted tumors of SCCKN cells, a human squamous carcinoma, were treated with a plasmid encoding E3C1. Plasmids were injected locally every week using a transfection reagent. Control mice treated with mock DNA started to be euthanized on day 18, because the tumors had grown to over 15% of the body weight, and all of them had died by day 43. On the other hand, the tumors in two of ten mice treated with E3C1 had disappeared. The other eight mice started to be euthanized on day 46 and eight of ten mice had been euthanized by day 197. After 18 days of therapy, the tumor volume of control mice was 2,804±829 mm(3) and that of the E3C1 mice was 197±159 mm(3). Histochemical studies showed enhanced apoptosis in the E3C1-treated tumors, as compared with controls. Changes in cell morphology and decreased polymerized actin induced by E3C1 indicated disturbed cell adhesion to the matrix. In in vitro studies of SCCKN cells, prolonged administration of an E3C1 recombinant protein to cultured cells reduced adhesion-independent growth of cancer cells, as compared with control cells. These data suggest that E3C1 treatment induces anoikis.